Urbanization and Nigerian economic development : proceedings of the 1977 Annual Conference of the Nigerian Economic Society. - Nigerian Economic Society (Ibadan, Nigeria : The Society, 1978)
This volume comprise of the proceedings of the 1977 Annual Conference of the Nigerian Economic Society (NSE) held under the theme: Urbanisation and Nigerian economic development. Sub-themes of the conference include:urbanisation and development-issues and perspectives; urbanisation-income distribution and employment problems; urban management problems and perspectives; urban transportation; problems of urban land use -housing and environment.
Includes bibliographies.
lje 22/1/19, ijb 06/02/2019
Loans
Keywords: Urbanization; Transportation; Unemployment; Housing; Rural-urban migration; Nigeria